Ag/SiO2 surface-enhanced Raman scattering substrate for plasticizer detection. (19th March 2018) - Wu, Ming-Chung; Lin, Ming-Pin; Lin, Ting-Han; Su, Wei-Fang
Abstract: In this study, we demonstrated a simple method of fabricating a high-performance surface-enhanced Raman scattering (SERS) substrate. Monodispersive SiO2 colloidal spheres were self-assembled on a silicon wafer, and then a silver layer was coated on it to obtain a Ag/SiO2 SERS substrate. The Ag/SiO2 SERS substrates were used to detect three kinds of plasticizer with different concentrations, namely, including bis(2-ethylhexyl)phthalate (DEHP), benzyl butyl phthalate (BBP), and dibutyl phthalate (DBP). The enhancement of Raman scattering intensity caused by surface plasmon resonance can be observed using the Ag/SiO2 SERS substrates. The Ag/SiO2 SERS substrate with a 150-nm-thick silver layer can detect plasticizers, and it satisfies the detection limit of plasticizers at 100 ppm. The developed highly sensitive Ag/SiO2 SERS substrates show a potential for the design and fabrication of functional sensors to identify the harmful plasticizers that plastic products release in daily life.